In situ sulfurized CoMoS/CoMoO4 shell–core nanorods supported on N-doped reduced graphene oxide (NRGO) as efficient electrocatalyst for hydrogen evolution reaction. Issue 6 (23rd January 2017) - Liu, Yan-Ru; Shang, Xiao; Gao, Wen-Kun; Dong, Bin; Li, Xiao; Li, Xue-Hui; Zhao, Jin-Chong; Chai, Yong-Ming; Liu, Yun-Qi; Liu, Chen-Guang
Abstract : In situ sulfurization of CoMoO4 nanorods supported on NRGO may be a promising strategy for excellent electrocatalyts for hydrogen evolution reaction (HER). Abstract : Many strategies, such as doping metal, designing low-dimensional nanostructures, and enhancing the utilization of active sites based on a conductive support, have been intensively pursued to improve the intrinsic activity of transition metal chalcogenides for the hydrogen evolution reaction (HER). However, integrating all the above-mentioned merits into one electrocatalyst is still a significant challenge. Herein, we have successfully prepared uniform CoMoS/CoMoO4 (CMS) shell–core nanorods, with a diameter of 60 nm and a length of 800 nm, supported on N-doped reduced graphene oxide (NRGO). The obtained CMS/NRGO can combine many advantages, including transition metal doping, one-dimensional nanorods, and the superior conductivity of NRGO, resulting in very promising HER properties and excellent stability. The optimum sulfurization temperature for unsupported CMS nanorods has been explored using uniform CoMoO4 nanorods as a precursor. Although CMS-3 prepared with a sulfurization temperature of 300 °C has been found to possess the optimum activity for the HER, when adopting NRGO as a support, CMS-3/NRGO exhibits an impressive enhancement in HER performances with a low overpotential of 80 mV, a small Tafel slope of 58 mV dec −1, and a large exchange current density of 428 μA cm −2 . In addition, the electrocatalytic activity of CMS-3/NRGO shows a negligible delay after 1000 cycles, indicating its robust electrochemical stability in acid electrolyte solution. Therefore, adopting low-temperature sulfurization of one-dimensional metal oxide precursors supported on NRGO may be a promising strategy for obtaining excellent electrocatalysts for the HER.